Kaolinite dating from Acrisol and Ferralsol: A new key to understanding the landscape evolution in NW Amazonia (Brazil) - Mathian, Maximilien; Bueno, Guilherme Taitson; Balan, Etienne; Fritsch, Emmanuel; Do Nascimento, Nádia Regina [UNESP]; Selo, Madeleine; Allard, Thierry (Elsevier, 2020)
Ferralsols and Acrisols are major types of soils of the Amazon basin observed on various landform units comprising plateau surfaces, incised hills at their edges and slopes. The present study focuses on an Acrisol developed on plateaus surfaces from northwest Amazonia and a Ferralsol from the convex hills of the incised plateau edges. Local geomorphologic models of weathering covers suggest that Ferralsols are younger than plateau Acrisols but the absolute chronology of their formation is still lacking. This type of information is however critical to understand the evolution of northwest Amazon Basin landscapes and to identify its link with major climatic and geomorphologic events. In this article, kaolinite-rich samples from soils and saprolites belonging to a transect in the São Gabriel da Cachoeira region (Amazon state, Brasil) are investigated. Based on their crystal-chemical characters, several types of kaolinites are identified. Using a previously developed methodology based on electron paramagnetic resonance (EPR) spectroscopy, crystallization ages are proposed for these different kaolinites. Saprolite kaolinites are dated from 6 to 3.6 Ma in the Acrisol profile and display significantly more recent ages (<1 Ma) in the Ferralsol saprolite. Kaolinite from solum (soils horizons above the C horizon) display ages ranging from 2.5 to 1 Ma for both the Acrisol and Ferralsol. Three distinct weathering stages are thus unraveled by kaolinite dating. The Acrisol saprolite displays the older weathering stage preserved in the investigated soil sequence. It is followed by a single weathering stage leading to the formation of both soils. These two stages can be correlated to the formation of two paleosurfaces recognized at the scale of the South America subcontinent as the Miocene Vehlas and the Quaternary Paraguaçu surfaces, indicating that the Curicuriari profiles evolved during periods favorable to tropical weathering surfaces development in Amazonia. The last weathering stage corresponds to the saprolite formation in the Ferralsol profile, which is still developing under the present Amazonian climate. This still active, late weathering stage is tentatively related to the more significant drainage and relief dissection occurring on the plateau edges.
Keywords: Amazonia; EPR dating; Ferralsol/Acrisol transition; Kaolinite; Laterite